2019
DOI: 10.1093/heapol/czz054
|View full text |Cite
|
Sign up to set email alerts
|

Institutional barriers and enablers to implementing and complying with internationally accepted quality standards in the local pharmaceutical industry of Pakistan: a qualitative study

Abstract: Complying with good manufacturing practices (GMP) and ensuring a quality system is integral to production and supply of quality medicines and achieving universal health coverage. This study focus on the local production of medicines in Pakistan, a lower middle-income country that has observed considerable growth in the number of pharmaceutical companies over the past two decades. Against this background, we investigated: (1) How is quality assurance (QA) and GMP compliance understood and acted upon by local ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Patient PV knowledge (barrier 11), or lack thereof, seemed to influence what PV-specific transgressions that pharmaceutical supply chain and its stakeholders could get away with in emerging economies (Ampadu et al. , 2018; Tauqeer et al. , 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient PV knowledge (barrier 11), or lack thereof, seemed to influence what PV-specific transgressions that pharmaceutical supply chain and its stakeholders could get away with in emerging economies (Ampadu et al. , 2018; Tauqeer et al. , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(5) In addition, PV-related KAP factors for patients in emerging economies (barriers 11, 12, and 13) were not comingled into one set as these barriers had varying levels of influences in our ISM-based hierarchical model due to driving and dependence powers that were comparatively dissimilar. Patient PV knowledge (barrier 11), or lack thereof, seemed to influence what PV-specific transgressions that pharmaceutical supply chain and its stakeholders could get away with in emerging economies (Ampadu et al, 2018;Tauqeer et al, 2019). Patient PV knowledge, along with pharmaceutical industry attributes, which in turn affected patient's attitude towards PV (barrier 12), ranged from socio-cultural beliefs (Eliasson, 2006) to cynicism towards PV reporting (Waring, 2005).…”
Section: Jamr 195mentioning
confidence: 99%
See 1 more Smart Citation
“…This is confirmed by the difficulty faced by LMICs when it comes to implementing certain guidelines such as the WHO’s good manufacturing practices. 98 Hence, other interventions must be appropriately adjusted and applied for implementation in LMICs. These include improvement of legal sanctions, increased stewardship, advocacy and regional cooperation in the implementation of international guidelines.…”
Section: Adaptation Of Interventions From Hics To Lmicsmentioning
confidence: 99%
“…A low manufacturing capacity for finished pharmaceutical products also means that most medicines would need to be imported, which can lead to the import of poor-quality medcines. In LMICs that do have a high local manufacturing capacity, quality may not always be assured, or the focus of the NRA may not be on quality assurance because of capacity challenges [ 46 , 47 ]. For example, in Pakistan, a study of twenty-seven ibuprofen API samples used by manufacturers in the country found that 81.5% (22/27) failed to comply with pharmacoepial specifications [ 48 ].…”
Section: Introductionmentioning
confidence: 99%